Metodología COBIT para el desarrollo de plan de gobernanza de Tecnologías de la Información y Comunicación en Hospitales Generales - Villacís Damacela, Juan Miguel (2023)
Today the Information Technologies have become a fundamental pillar of organizations, institutions and companies; Its use increased where technology plays an important role in the development of organizational activities where in several cases, the presence of the user and the service operator is no longer necessary, everything has become telecare. Existing regulations governing institutions are supported by a properly structured IT governance; The present investigation develops an IT governance plan in the Information and Communication Technologies Unit of the Ambato General Hospital for the control and achievement of institutional goals, the information collected through a descriptive qualitative approach and the analysis with the COBIT 2019 methodology achieves establish a plan as a reference framework in IT governance that involves all users in processes that generate value for the organization, reduce risks and optimize resources that allow the viability of the scope and achievement of goals in the entity; plan that is verified with the calculation of the reliability coefficient and the evaluation by experts in topics of theoretical foundation, relevance and methodological coherence, feasibility and importance.